1998
DOI: 10.1007/bf02317817
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and structure of dihydrazones obtained from the dihydrazide of S,S′-(1,3,4-thiadiazole-2,5-diyl)bis(2-mercaptopropionic acid)

Abstract: It has been established by PMR spectroscopy that dihydrazones obtained by the condensation of the dihydrazide of S,S'-(l,3,4-thiadiazole-2,5-diyl)bis(2-mercaptopropionic acid) with aldehydes, ketone.s, and B-dicarbonyl compounds exist in solution as a mixture of stercoisomeric forms, the ratio of which depends on the structure of the carbonyl compound used in the condensation. E',Z'-conformational (twisting) isomerism due to hindered rotation about an N--CO amide bond and E,Zgeometric syn-and anti-isomerism re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Conformational isomerism of hydrazones obtained from 2,5-dimercapto-1,3,4-thiadiazole has been studied previously [12,13]. Hydrazones in solution exist as a mixture of two conformers (anti/syn), as exemplified by doubled proton resonances assigned to the CH 2 CO, =CH and NH groups in 1 H NMR spectra.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Conformational isomerism of hydrazones obtained from 2,5-dimercapto-1,3,4-thiadiazole has been studied previously [12,13]. Hydrazones in solution exist as a mixture of two conformers (anti/syn), as exemplified by doubled proton resonances assigned to the CH 2 CO, =CH and NH groups in 1 H NMR spectra.…”
Section: Resultsmentioning
confidence: 99%
“…The percentages of anti -and syn -conformers are calculated from the ratio of integral intensities of these signals. It was found that syn -conformers dominate in DMSO solution [12][13][14].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation